Sosialisasi Bahan Bulan Kitab Suci Nasional 2023 Dan Penyegaran Fasilitator Katekese Umat Di Paroki Santo Kristoforus Ba’a Rote - Yofince Abatan; Dorince Oetpah (CV. Multi Kreasi Media, 2023)
One of the national movements implemented by the Indonesian Catholic Bishops' Conference for Catholics throughout Indonesia is National Scripture Month which falls in September. During this month, Indonesian Catholics under the coordination of the Indonesian Biblical Institute held catechesis activities to encourage people to read and love the Word of God in the Holy Bible. In 2023, National Scripture Month will be held under the theme